Exploring a community’s socio-economic experiences of coal mining - Jurgens, Racheal Melisa (Rhodes University, 2026)
As a vital non-renewable resource, coal plays a major role in economic growth but frequently presents serious social and environmental problems. Coal mining has changed Schoongezicht, Witbank, Mpumalanga's socioeconomic structure, bringing opportunities and difficulties for the local population. The effects of coal mining on the livelihoods, social structures, and health of Schoongezicht residents are examined in this study, emphasising older people who have been exposed to mining-related changes for an extended period. Three main goals serve as the foundation for this study: how coal mining affects local livelihoods, how social dynamics in the community are changing, and how mining operations affect health. In-depth interviews were incorporated into the qualitative methodology. Data were triangulated with secondary sources, such as government documents, news articles, and previous research, and participants were chosen using purposive and snowball sampling techniques to capture a range of viewpoints. According to the findings, although some households have benefited economically from coal mining, the larger community still faces many difficulties. Traditional livelihoods are being undermined, job inequality is rising, and social cohesion is being disrupted. Air and water sources have become contaminated due to environmental degradation, making health problems like respiratory illnesses worse, especially for elderly residents. Furthermore, because mining companies and government institutions are not responding to the health needs of the community, people frequently turn to traditional remedies, which further restricts access to healthcare. Furthermore, the disturbance of customary means of subsistence and communal cohesiveness highlights the intricate and frequently incongruous consequences of coal mining in the area. This dual reality draws attention to the conflict between the long-term costs suffered by vulnerable populations and the promise of progress.
the case of Schoongezicht in Witbank, Mpumalanga
Keywords: Socio-economic status (http://id.loc.gov/authorities/subjects/sh85124191); Coal mines and mining (http://id.loc.gov/authorities/subjects/sh85027364); Witbank (South Africa) (http://id.loc.gov/authorities/names/n80034245); Mineral industries--Environmental aspects (http://id.loc.gov/authorities/subjects/sh85085556); Livelihood (https://www.wikidata.org/wiki/Q6658164); Social dynamics (https://www.wikidata.org/wiki/Q304922)